(untitled) (Journal of Social Sciences Review, 2025)
The aim of this research was to assess how power training and resistance affect medium-fast bowlers’ bowling speed in cricket. Because of their capacity to create pace, medium-fast bowlers are vital in cricket; nevertheless, it’s not known whether power training or resistance can really improve their bowling speed. This research included twenty medium-fast bowlers from cricket clubs of the Sports Board Punjab, aged between twenty and 25 years. Under a pre-test and post-test quasi-experimental design, bowling speeds were assessed using a speed gun both before and after an 8-week resistance and power training intervention. Emphasizing strength and plyometric activities meant to increase explosive power, the training sessions included moderate to high-intensity workouts. The mean speed of the participants improved significantly; from 118.75 km/h in the pre-test to 126.65 km/h in the post-test. A paired sample t-test revealed statistical relevance with a 0.000 p-value. A somewhat smaller range in bowling speed points to more consistent bowlers. Training was validated by pre-test and post-test speeds showing a modest positive correlation. The results imply that power and resistance training can increase the bowling speed of medium-fast bowlers, hence improving cricket performance. Bowlers were advised by coaches and trainers to include such drills to raise their performance. Long-term effects of this training on bowling speed and injury avoidance should be investigated in next studies. Keywords: Bowling Speed, Resistance Training, Power Training, Medium-Fast Bowlers.